Soft Metal Cations Trigger Sandwich‐Cluster Luminescence of a New Au(I)‐Vinylimidazolate Cyclic Trinuclear Complex. Issue 8 (22nd February 2022) - Lu, Zhou; Burini, Alfredo; McDougald, Roy N.; Ricci, Simone; Luciani, Lorenzo; Nesterov, Vladimir N.; Rawashdeh, Abdel‐Monem M.; Omary, Mohammad A.; Galassi, Rossana
Abstract: The formation of heterobimetallic complexes from parent cyclic trinuclear complexes (CTCs) of gold(I) has become straightforward in recent years with this team and others showing that the strategy leads to strengthened Au−M' bonding and optoelectronic properties. A new gold(I)‐vinylimidazolate CTC, 1, was prepared and the formation of highly emissive sandwich adducts with the soft metal cations Cu +, Ag +, and Tl +, 2 –4, respectively, was investigated. Compound 1 does not exhibit peculiar emissive properties at room or cryogenic temperatures as the adducts do. Its unit cell packing displays an unprecedented collection of repeating units for CTCs. While the intermolecular Au…Au distances are versatile (3.470, 3.673, and 4.045 Å), they connect only single Au centres from adjacent CTCs and form extended circular networks. Hirshfeld surface analyses mapped the new CTC contours underlining the possible cooperative effects of not only metallophilic interactions but also C−H…π and hydrogen bonding in the packing of 1 (as opposed to the dominance of the former in most other reported CTCs). DFT calculations validate the formation of sandwich‐like structures for compounds 2 –4 with averaged Au−M distances of 2.665 Å, 2.802 Å, and 3.036 Å, respectively, close by to experimental crystal data obtained for similar sandwich compounds. Abstract : CTCs (cyclic trinuclear complexes) are becoming interesting substrates to prepare materials exhibiting intriguing and multi‐variable optoelectronic properties, including varying chemical composition, the excitation wavelengths and/or the temperature. A new CTC, tris(vinylimidazolatogold(I)), 1, was synthesize and structurally characterized, exhibiting fascination supramolecular structure with both vertical and horizontal aurophilic bonding in pseudo‐2D/3D networks. While 1 displays weak emission properties, it intensively glows upon 2 : 1 stoichiometric reactions with Cu +, Ag + or Tl + ions. Computational studies confirm the sandwich‐like structure for all such cation‐π adducts and characterize all mutually reinforcing supramolecular interaction types in 1 .